2015
DOI: 10.1159/000441988
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic and Environmental Factors Underlying Hypospadias

Abstract: Hypospadias results from a failure of urethral closure in the male phallus and affects 1 in 200-300 boys. It is thought to be due to a combination of genetic and environmental factors. The development of the penis progresses in 2 stages: an initial hormone-independent phase and a secondary hormone-dependent phase. Here, we review the molecular pathways that contribute to each of these stages, drawing on studies from both human and mouse models. Hypospadias can occur when normal development of the phallus is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
154
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 196 publications
(254 reference statements)
3
154
0
4
Order By: Relevance
“…Given that conditions associated with a defect in the androgen receptor (AR) are more likely to be associated with multiple hypospadias surgery [Lucas-Herald et al, 2016], it is plausible that the increased rate of complications in cases of proximal hypospadias may be partly related to the effect that reduced androgen exposure may exert during critical periods of prenatal development. In cases of hypospadias, extra-genital anomalies may also be part of a constellation that points towards a specific genetic aetiology [van der Zanden et al, 2012;Bouty et al, 2015]. For instance, cases of XY DSD with normal gonadal function that are small for gestational age are less likely to have a mutation in the AR gene [Poyrazoglu et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that conditions associated with a defect in the androgen receptor (AR) are more likely to be associated with multiple hypospadias surgery [Lucas-Herald et al, 2016], it is plausible that the increased rate of complications in cases of proximal hypospadias may be partly related to the effect that reduced androgen exposure may exert during critical periods of prenatal development. In cases of hypospadias, extra-genital anomalies may also be part of a constellation that points towards a specific genetic aetiology [van der Zanden et al, 2012;Bouty et al, 2015]. For instance, cases of XY DSD with normal gonadal function that are small for gestational age are less likely to have a mutation in the AR gene [Poyrazoglu et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Hypospadias is a common congenital anomaly affecting approximately 1 in 300 male births [Ahmed et al, 2004], and its underlying aetiology may be multifactorial [Bouty et al, 2015]. Several congenital conditions that are associated with a disorder of sex development (DSD), including a disorder of gonadal development, disorder of androgen synthesis, or disorder of androgen action, can be associated with hypospadias [Ahmed et al, 2016].…”
Section: © 2019 S Karger Ag Baselmentioning
confidence: 99%
“…Recently WNT7B and WNT9B were found to be regulators of ureter development in a mouse model system [10] and WNT3 was shown to be involved in bladder exstrophy in zebrafish [11]. WNT signalling is also involved in the development of the genital tubercle and impairment of WNT signalling can result in malformations of the urethra and hypospadia [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, SRD5A2 (steroid 5 alpha-reductase 2), MAMLD1 (mastermind like domain containing 1), and AR (androgen receptor) have been studied in human cases of hypospadias [Bouty et al, 2015], while AR polymorphisms also showed an association with cryptorchidism [Docampo and Hadziselimovic, 2015]. Moreover, mutations of AR and SRD5A2 can be also responsible for penis underdevelopment [Cimador et al, 2015].…”
mentioning
confidence: 99%